Buffy Coats of Kacang Goats Slaughtered at A Traditional Slaughterhouse in Western Denpasar - Iwan Harjono Utama; Radhita Andriani; Siswanto Siswanto (Institute for Research and Community Service, Udayana University, 2017)
This study examines the buffy coat of local Kacang goats slaughtered in a traditional slaughterhouse in Western Denpasar. The blood of 20 male Kacang goats was collected using a survey method, with randomized sampling. Inclusion in the study was based on the health status of the goats, but there were no requirements concerning diet or management systems. Once collected, blood was stored in tubes containing ethylenediamine tetraacetic acid anticoagulant. Buffy coats were evaluated using the Westergren erythrocyte sedimentation method. Four of the 20 blood samples had buffy coats with 0 mm/24 h thickness, two of the blood samples had 1 mm/24 h thickness, eight samples had a buffy coat thickness of 2 mm/24 h, and three of the samples had a buffy coat sickness of 4 mm/24 h. Thirteen samples had a graywhite colored buffy coat, three samples had a pink buffy coat, and the remaining three samples had a clear buffy coat.